Detection Limit of Surface Plasmon Resonance Sensor for Quantitative Foodborne E.coli Detection Using Effective Refractive Index Theory : The theoretical limit of E.coli detection of surface plasmon resonance - Nattha Pensupa; Treesukon Treebupachatsakul; Chanin Lochotinunt; Suejit Pechprasarn (My University, 2021)
Surface plasmon resonance has been a gold standard for label-free biomedical and biochemical measurements, such as protein binding kinetics, protein-protein interactions. The surface plasmon resonance has also been utilized in food safety screening, including Escherichia coli and Salmonella detection. The theory of surface plasmon resonance has been well established and demonstrated its ultra-sensitivity to detect small nucleotides, proteins, and molecules. However, the results, so far, for the E.coli detection under the surface plasmon resonance have not shown an impressive detection limit. The typical detection limit of $E. c o l i$ under the conventional surface plasmon detection platform is around $10^{3} \mathrm{CFU} / \mathrm{ml}$. The detection limit can be enhanced using a secondary binding agent to E.coli, including conjugated nanoparticles. Here, we propose a theoretical framework using effective refractive index theory to explain the detection mechanism and give an insight into the underlining obstacles that degrades the detection limit of the surface plasmon resonance.
Keywords: Biosensors and Analytical Detection; Advanced biosensing and bioanalysis techniques; Plasmonic and Surface Plasmon Research